Renewable Economies in the Arctic - Natcher, David C.; Koivurova, Timo (Routledge Research in Polar Regions, 2022)
"This book offers multidisciplinary perspectives on renewable economies in the Arctic and how these are being supported scientifically, economically, socially, and politically by Arctic states. The economic development of the Arctic region is witnessing new, innovative trends which hold promise for the sustainable development of the region. This book discusses the emerging forms of renewable economies to understand where intellectual and technological innovations are being made. It draws on the expertise of scholars from across the Arctic and provides the reader with a foundation of knowledge to identify the unique challenges of the region and explore opportunities to unlock the immense potential of renewable resources to boost the region's economy. This book offers a holistic Arctic perspective against the backdrop of prevailing social, economic, and climatic challenges. With critical insights on the economic state of play and the role of renewable resources in the development of the Arctic region, this book will be a vital point of reference for Arctic scholars, communities, and policy makers."